Geographical characteristics influencing the risk of poisoning in pet dogs: Results of a large population-based epidemiological study in Italy. (May 2018) - Calzetta, L.; Roncada, P.; Piras, C.; Soggiu, A.; Liccardi, G.; Mattei, M.; Pistocchini, E.
Highlights: A large population-based epidemiological study on poisoning in dogs was performed. Retrospective results were validated via a prospective approach. Altitude and habitat predicted the risk of poisoning. A high risk index was found for strychnine and metaldehyde in hill country. Seashore territories were at high risk index for anticoagulants. Abstract: Pets can act as sentinels for human health and thus surveillance of pet dogs has the potential to improve awareness of emerging risks for animal and public health. The aim of this study was to investigate factors associated with the risk of canine poisoning. In a large population-based epidemiological investigation in Italy performed from January 2015 to January 2016 and April 2016 to April 2017, descriptive statistics were acquired and analysed to determine variables associated with poisoning events in pet dogs. Results were validated in a test population and forecast analysis of risk was performed. The cumulative incidence of poisoning events was low (10.2/1000 dogs/year). Anticoagulant rodenticides, organophosphate pesticides, metaldehyde and strychnine were the most frequent causes of intoxications. Territory characteristics significantly modulated both the frequency and the nature of the involved substances. The seashore area was associated with poisoning by rodenticides (odds ratio, OR, 1.81, 95% confidence interval, CI, 1.54–2.13) and metaldehyde (OR 1.61, 95% CI 1.16–2.28). The hill country area was associated with poisoning by organophosphate pesticides (OR 1.73, 95% CI 1.38–2.15), metaldehyde (OR 2.26, 95% CI 1.53–3.25) and strychnine (OR 1.86, 95% CI, 1.34–2.57). The mountain area was associated with strychnine poisoning (OR 3.79, 95% CI 2.84–5.06). The prospective cumulative incidence of poisoning over 10 years was 9.74% (95% CI 9.57–9.91). These results may be useful for predicting the risk of poisoning and for estimating the risk index related to specific toxic compounds in specific territories. This study suggests that poisoning events in dogs may represent a problem of public health with the potential to affect wildlife and human beings.